Tinjauan Potensi dan Tantangan Penerapan Teknologi Blockchain dalam Sistem Hukum - Hidayat, Hermawan; Van Gobel, Abdul Azis; Moonti, Roy Marthen; Kasim, Muslim A. (Lembaga Pengembangan Kinerja Dosen, 2025)
Transparency and accountability in the legal system remain critical challenges in the ongoing efforts to reform governance in the digital era. This article aims to examine the potential and challenges of implementing blockchain technology to enhance transparency and accountability within legal systems. The study employs a qualitative literature review approach, conducting an in-depth analysis of relevant scientific literature and recent publications. Findings reveal that blockchain offers innovative solutions through immutable legal data and decentralized processes, which enhance public trust and efficiency via smart contracts and decentralized dispute resolution systems. However, the implementation of this technology faces obstacles related to regulation, data privacy, and the need for adequate infrastructure development. In conclusion, blockchain has the potential to revolutionize the legal system, provided there is cross-sector collaboration to overcome existing barriers. Further research is recommended to integrate empirical methods and case study explorations to deepen and apply understanding of blockchain adoption in legal contexts.